Determinants of complications in adolescent pregnancies: a cross-sectional analytical study in three hospitals in Yaoundé - Félix, Essiben; M. Ange, Ngo D.; Evelyne, Umuhire; Léonard, Mol H.; Pascal, Foumane (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adolescent pregnancy remains a pressing public health issue in Cameroon, contributing significantly to maternal and neonatal complications. Understanding the determinants of these complications is crucial to improving care and outcomes for pregnant adolescents in Yaoundé. The objective of the study was to describe the key sociodemographic, clinical, and healthcare-related factors associated with complications among pregnant adolescents in Yaoundé. Methods: We conducted a prospective, hospital-based cross-sectional analytical study over eight months (October 2024–June 2025) in three hospitals in Yaoundé. The study involved adolescent girls aged 15–19 years attending antenatal care or birthing at these sites. Data were collected using pretested questionnaires and analysed using Stata SE17 and R 4.4.3, with statistical significance set at p<0.05. Results: Out of 215 adolescent mothers enrolled, 22% experienced complications, with perineal lacerations (30.7%) and low birth weight (21.9%) being the most common maternal and foetal complications respectively. Significant independent risk factors for complications included having fewer than 4 antenatal care visits (aOR=3.75, p=0.011) and unemployed partner or working in the informal sector (aOR=7.60, p=0.008). Additionally, receiving good preventive care during ANC was found to be a protective factor (OR=0.21, p=0.015). Other factors such as age, education level, history of abortion, and partner support were not significantly associated with complications. Conclusion: Adolescent pregnancy is subject to overlapping socioeconomic and healthcare limitations, leading to high maternal and neonatal complications despite hospital-based deliveries. Addressing these outcomes requires adolescent-centered, multidisciplinary management including by families, clinicians, researchers, and government policies.